The Demand for Reinsurance in U.K. Non-Life Insurance Industry: Theory and Empirical Tests - ZHANG, YU (2013)
This study is aimed to investigate the determinants of reinsurance purchasing in the U.K. non-life insurance industry. By using the data on 276 U.K. non-life insurers during the period of 1989-2010, it empirically tests the 11 theoretical potential firm-special factors that affecting the demand for reinsurance. Based on fixed effect model and binary regression model, it indicates underwriting risk, profitability, size, earning volatility, and product concentration have a strong impact on reinsurance purchasing for the U.K. non-life insurance firms, which suggest reinsurance enable insurers to mitigate underwriting risk, bankruptcy risk and probability in raising new external funds, to increase the underwriting capability and flexibility, and to access professional and relatively cheap services. In contact, tax related factors and organization form are found to have no significant impact on the reinsurance purchasing, and there also no support is found for the theoretically expected effect of leverage, growth opportunity, and liquidity on reinsurance demand.